O RECURSO DE AGRAVO NO ORDENAMENTO JURÍDICO BRASILEIRO: DA ORIGEM AO CÓDIGO DE PROCESSO CIVIL DE 1939 - Carvalho, Fernando Ribeiro da Silva (2020)
This study aims to analyze the trajectory of a specific legal instrument, the interlocutory appeal. The survival of such a long-standing legal instrument in Portuguese-Brazilian culture qualifies as the problem. It´s been sought to be presented different